Ultrasonic Machining: A Comprehensive Review of Principles, Applications, and Limitations - Kumar, Pardeep (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 11 No 3&4 (2024): Journal of Advanced Research in Instrumentation and Control Engineering, 2025)
Ultrasonic Machining (USM) is an unconventional machining technique that removes material from workpieces with exceptional efficiency and precision by using high-frequency mechanical vibrations. The USM process, its elements, and its uses are thoroughly examined in this review paper. The paper discusses the advantages of USM, including high precision, low cost, high speed, minimal noise, and reduced tool wear. However, it also highlights the limitations of USM, such as low material removal rate, high energy requirements, difficulty in machining soft materials, limited deep hole drilling, and high tool wear rate. The paper also explores the different types of USM, including Rotary Ultrasonic Machining (RUM) and Chemical Assisted Ultrasonic Machining (CUSM), and their applications in various industries. Additionally, the paper discusses Ultrasonic Micro Machining (USMM), a technique used to machine micro components with complex features, and its advantages and limitations. Overall, this review paper provides a comprehensive overview of the USM process, its capabilities, and its limitations, making it a valuable resource for researchers and industry professionals seeking to understand and utilize this versatile machining technique.